Impact of hydraulic and physicochemical factors on spatiotemporal variations of particle-associated bacteria in a drinking water distribution system - Osborne, Erika; Haddix, Madison; Garner, Emily (Frontiers in Water, 2022)
Drinking water distribution systems are critical infrastructure that protect public health by ensuring safe water is transported from centralized treatment facilities to consumers. While growth of bacteria in distribution system infrastrucutre is well established as a detriment to water quality, little is known about the role of sediment in conveying bacteria via biofilms throughout these systems. The objective of this study was to quantify the abundance of sediment-associated bacteria in a rural drinking water distribution system with a chlorine disinfectant residual. The role of hydraulic and physicochemical factors in influencing the loading of sediment-associated bacteria in the system was also examined. The concentration of sediment-associated bacteria averaged 1.28 log10 gene copies per mL, while total bacteria averaged 2.16 log10 gene copies per mL, demonstrating that biofilms formed on the surface of sediment represent a substantial portion of overall loading in the studied distribution system. Total suspended solids concentrations were correlated with sediment-associated bacteria, but not total bacteria. Pipe diameter was found to be an important factor associated with the abundance of both total and sediment-associated bacteria, as well as total chlorine concentration. Flow regime (i.e., the magnitude of flowrate variation) was also found to be important, as it was associated with both sediment and total bacteria, but not sediment-associated bacteria. The results of this study indicate that sediment-associated bacteria and total bacteria concentrations often followed disparate trends, demonstrating that their abundance is differentially influenced by a complex combination of physicochemical and hydraulic factors. These findings help to establish sediment as an important conduit for microbial loading in a chlorinated drinking water distribution system.